Shared intentionality and divine persons: explorations in empirical psychology and ramified natural theology - Bray, Dennis P. (Religious studies, 2025)
This article explores the intersection of two developing fields of study: the psychological field of shared intentionality and the philosophy of religion field of ramified natural theology. In shared intentionality, agents share mental states and cooperate to achieve a common goal. Many psychologists in this field believe that of all the primates, only humans share intentionality - humans alone form a "we". Ramified natural theology is the project of presenting philosophical evidences for core doctrines of the Christian faith. In this article I investigate some applications of shared intentionality for Christian natural theology. In the Anselmian tradition I offer two deductive arguments that deploy shared intentionality to argue that there are multiple divine persons. I then suggest that analogical arguments - often overlooked by philosophers of religion - provide a better fit for psychological findings, such as shared intentionality. After sketching some fundamental features of analogical arguments, I advance two arguments by analogy for the conclusion that God, like humans, shares intentionality. These arguments show that the psychology of shared intentionality, and empirical psychology more generally, is a promising source for theological reflection.